2022
DOI: 10.1111/1440-1681.13694
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro redox adaptation model for metastatic prostate cancer: Establishing, characterizing and Cabazitaxel response evaluating

Abstract: Little is known about the redox-adapted cancer cells for understanding their pharmacologically targetable features and chemotherapeutic responses. Thus, we present the first in vitro redox adaptation model for metastatic prostate cancer (mPC), LNCaP-hydrogen peroxide resistant (LNCaP-HPR), with enhanced oxidative stress resistance accompanying poor Cabazitaxel response. After establishing, the cells were characterized by comparing the viability, death, oxidative stress, total glutathione (GSH) levels and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Moreover, after the adaptation, the Cab response of the redox-adapted cells also resembled those of more aggressive C4–2 mCRPC cells, unlike LNCaP. 12 This time, the association between the apoptotic effect of Cab and its pro-oxidant efficacy on the redox adaptation mechanisms in PC cells has been evaluated. Moreover, being reported that the oxidative stress states of PC cells were directly proportional to the aggressive characteristics, 16 we used four cells with different aggressivity, including LNCaP mPC, redox-adapted LNCaP-HPR mPC, C4–2 mCRPC, and RWPE-1 benign cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, after the adaptation, the Cab response of the redox-adapted cells also resembled those of more aggressive C4–2 mCRPC cells, unlike LNCaP. 12 This time, the association between the apoptotic effect of Cab and its pro-oxidant efficacy on the redox adaptation mechanisms in PC cells has been evaluated. Moreover, being reported that the oxidative stress states of PC cells were directly proportional to the aggressive characteristics, 16 we used four cells with different aggressivity, including LNCaP mPC, redox-adapted LNCaP-HPR mPC, C4–2 mCRPC, and RWPE-1 benign cells.…”
Section: Discussionmentioning
confidence: 99%
“…The C4–2 mCRPC cells were kindly provided by Dr. Thalmann from the Urology Department, University of Bern. LNCaP-H 2 O 2 resistant-(HPR) cells were established by continuously applying 50 μM H 2 O 2 to parental LNCaP cells as we reported previously, 12 and the H 2 O 2 concentration to which the cells adapt was added to the complete media. The culture conditions were previously reported for LNCaP, LNCaP-HPR, and C4–2 cells.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations